Influence of Anthropogenic Pressure on the Plant Species Richness and Diversity Along the Elevation Gradients of Indian Himalayan High-Altitude Protected Areas - Bisht, Monika; Chandra Sekar, K.; Mukherjee, Sandipan; Thapliyal, Neha; Bahukhandi, Amit; Singh, Divya; Bhojak, Puja; Mehta, Poonam; Upadhyay, Shashi; Dey, Dipti (Frontiers in Ecology and Evolution, 2022)
Plant biodiversity of some of the high-altitude national parks of Indian Himalaya are increasingly experiencing anthropogenic pressure. Consequently, plant species composition, vegetation structure, and diversity patterns of these protected areas are assumed to be substantially altered. However, limited efforts are made to quantify impact of anthropogenic disturbances on the species richness of such high-altitude national parks of Indian Himalaya. In order to overcome this data gap, the present study is aimed at quantifying the impact of anthropogenic disturbances on the vegetation community patterns of two National Parks of Himalaya along elevation gradients (3200-4500m asl), i.e., Valley of Flowers National Park and Great Himalayan National Park, India. Plant species richness and diversity patterns along altitude gradient exhibited significantly lower values in disturbed sites. Similarly, disturbed sites were noted to have lower numbers of threatened and endemic species (20 & 17, respectively) in comparison to undisturbed sites (32 & 31, respectively). The disturbed sites of lower elevation zones (3200-3500 m) of both parks were found with higher density of invasive species (i.e., Polygonum polystachyum, Impatiens sulcata, Cuscuta europaea, etc.). Diversity (Hill numbers) profiles between disturbed and undisturbed sites also showed contrasting patterns in species evenness, with VoFNP exhibiting more variation attributed to high level of disturbance. The non-metric multidimensional scaling of species composition data along elevation indicated that heterogeneously grouped plant species were much higher for disturbed sites than undisturbed ones. The quantum of anthropogenic pressure on disturbed sites were discernible through statistically significant lower values of soil moisture, bulk density, porosity, potassium and phosphorous content than the undisturbed sites. The canonical correlation analyses of species compositions and soil properties indicated that soil moisture and pH were the two major factors controlling species composition for both disturbed and undisturbed sites, whereas soil porosity played major role in species composition of undisturbed sites. Our study indicated that anthropogenic pressures on the high-altitude national parks of India not only altered the soil properties, but potentially threatened the species composition, thus accelerating urgent need to implement mitigation measures for restoration of degrading habitat of the native, endemic, and threatened plants in both the Parks.